Skin Grafts for Residual Limb Coverage and Preservation of Amputation Length. Issue 3 (September 2015) - Polfer, Elizabeth M.; Tintle, Scott M.; Forsberg, Jonathan A.; Potter, Benjamin K.
Abstract : Background: Split-thickness skin grafts have historically been used sparingly for amputation coverage when delayed primary closure is not feasible without substantial loss of length. The authors investigated the use of split-thickness skin grafts in the residual limbs of combat-related amputees. Methods: A retrospective review was completed on consecutive amputations of 300 lower and 100 upper extremities treated at Walter Reed National Military Medical Center from 2003 to 2009, comparing patients treated with split-thickness skin grafts with those treated with delayed primary closure. Principal outcomes measured included early (wound failure) and late (heterotopic ossification requiring excision and soft-tissue revisions) complications requiring surgery. Results: Statically significant differences were seen, with the split-thickness skin graft group having an increased incidence of wound failure ( p < 0.022), heterotopic ossification requiring excision ( p < 0.001), and soft-tissue revisions ( p < 0.001) compared with controls. The risk of revision was higher for lower extremity than for upper extremity amputations undergoing skin grafting. However, amputation level salvage, maintaining the proximal joint, was successful for all residual limbs with split-thickness skin grafts. Conclusions: Split-thickness skin grafts for closure of amputations result in significantly increased reoperation rates, but they are ultimately successful in salvaging residual limb length and amputation levels. In carefully selected patients, they may be a successful means of achieving definitive coverage when performed over robust, healthy muscle. In many patients, however, they should be viewed as a staging procedure to maintain length and amputation level until swelling decreases and revision surgery for split-thickness skin graft excision with or without concurrent procedures can be performed without the need to substantially shorten the residual limb. Abstract : Coding Perspective for this article is on page 608.